A need for orientation: The WMA statement on natural variations of human sexuality. (3rd September 2015) - Mahler, Lieselotte; Mundle, Goetz
Abstract: An alarming stigmatization and discrimination of homosexual people persists despite the formal depathologization of homosexuality, which occurred through the removal of the diagnosis from the DSM- (1973) and classification from the ICD (1991). The adoption of an expedited Statement on sexual orientation by the majority at the 64th General Assembly of the WMA is therefore an important and overdue measure. The Statement clearly asserts, among other things, that homosexuality is not an illness and therefore requires no cure. It also suggests that direct and indirect discrimination and stigmatization of people due their sexual orientation often leads to psychological and physical illnesses. Furthermore, delegates of the WMA condemned so-called reparative or conversion "therapies", which strive to induce heterosexual or asexual behavior. These are not only ineffective and unethical, but are strongly associated with serious negative impacts on health. Such a statement from the World Medical Association (WMA) is of particular importance as ambivalence and uncertainty in regards to homosexuality exists even within the medical and therapeutic professions. The latent or manifest attribution of homosexuality as an illness or developmental disorder is still widespread. One possible explanation for this may be the disruption of an open and sustainable discourse on causes, effects and definitions of sexual orientation following the "official depathologization". Especially those working in the medical and therapeutic contexts should be aware of their special responsibility not to pathologize homosexuality.